Assessment of the Attitude and Barriers of Iraqi Community Pharmacists to Provide Vaccination Services - Kadhim, Dheyaa Jabbar (Iraqi Journal of Pharmaceutical Sciences, 2024)
Abstract Since the focus of healthcare has shifted toward prevention, pharmacists were highly encouraged to expand their practice to include vaccination services. The aim of the current study was to evaluate the attitude of Iraqi community pharmacists to provide vaccination and to explore the expected barriers to provide such services at community setting. The present study was a cross-sectional online survey study that included 135 Iraqi community pharmacists who are licensed by the Iraqi syndicate of pharmacists. The first part of the survey questionnaire is related to sociodemographic characteristics. The 2nd part assessed the attitudes of community pharmacists towards delivering vaccination service in community pharmacy setting. The 3rd section explore barriers that community pharmacists expected to face when delivering vaccines. Among the 135 participants, 59 (43.7%) showed high positive attitude and 65 (48.14%) reported high barriers level. Only (45.93%) of respondents agreed that community pharmacists have a good knowledge about vaccination and only (42.22%) of them agreed that vaccination by community pharmacists will lower the cost to the patients. In addition, (79.26%) of them agreed that providing vaccination through community pharmacy will improve the rate of vaccination in general. Regarding barriers, results of the current study showed that the most common two barriers to provide vaccination services were lack of authorization and lack of continuous training and workshops [(85.19%) for each]. Pharmacists with Bachelor degree had significantly higher positive attitude compared with those having higher academic degrees. In addition, pharmacists with working experience of 5 years or less had significantly higher barrier score compared to those with more than 5 years working experience. In conclusion, despite their desire to increase their knowledge, less than half of Iraqi community pharmacists reported a positive attitude toward the introduction of a community-based vaccination program. In addition, many barriers about implementing vaccination services were found in the current study.